2022
DOI: 10.1108/ijilt-09-2021-0144
|View full text |Cite
|
Sign up to set email alerts
|

A data mining approach using machine learning algorithms for early detection of low-performing students

Abstract: PurposeThe purpose of the study is to build predictive models for early detection of low-performing students and examine the factors that influence massive open online courses students' performance.Design/methodology/approachFor the first step, the author performed exploratory data analysis to analyze the dataset. The process was then followed by data pre-processing and feature engineering (Step 2). Next, the author conducted data modelling and prediction (Step 3). Finally, the performance of the developed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…The ML is a branch of artificial intelligence that deals with the development of algorithms and techniques that enable computers to learn from data and improve their performance over time (Khor, 2022). There are different types of machine learning algorithms, such as supervised learning, unsupervised learning, and reinforcement learning.…”
Section: Methodsmentioning
confidence: 99%
“…The ML is a branch of artificial intelligence that deals with the development of algorithms and techniques that enable computers to learn from data and improve their performance over time (Khor, 2022). There are different types of machine learning algorithms, such as supervised learning, unsupervised learning, and reinforcement learning.…”
Section: Methodsmentioning
confidence: 99%
“…This theory involves the use of various techniques and tools, such as high-contrast color schemes, alternative text descriptions, and screen-reader compatibility, to ensure that users with visual disabilities can access and navigate through digital content without any barriers. By implementing visual accessibility principles, organizations can ensure that their products and services are inclusive and accessible to all users, regardless of their visual abilities [5] .…”
Section: Definition and Explanation Of Visual Accessibility Theorymentioning
confidence: 99%
“…Meanwhile, machine learning techniques have been leveraged to analyse data from VLEs to forecast student performance and examine factors affecting it. For example, Khor (2022) built predictive models using machine learning algorithms and VLE data for the identification of slow-progressing students, and the study found that the academic background and VLE interactions are important features for the prediction of students' academic performance. By analysing VLE data along with the attendance and grades of students, Leino et al (2021) showed that the overall activity within the VLE along with the performance of students in online tests and interaction with lecture recordings were key predictors of student achievement in psychology education.…”
Section: Introductionmentioning
confidence: 99%